Tax Avoidance And Green Accounting In Increasing Firm Value And CSR Practices In Indonesia - Hendra Galuh Febrianto; Januar Eky Pambudi; Dede Sunaryo; Amalia Indah Fitriana; Sandrina Dehavilan (Jurnal Reviu Akuntansi dan Keuangan, 2025)
Purpose: This study investigates the impact of tax avoidance and green accounting on corporate value, with Corporate Social Responsibility (CSR) serving as a moderating variable. Methodology/approach: The research involved is included in quantitative analysis. This study covers the population of 83 energy companies on IDX. This sampling technique uses purposive sampling in 50 company financial statement data samples. Data analysis was done using panel data analysis, and the MRA test was performed using Eviews 12. Findings: The study findings suggest that avoiding taxes has little effect on the value of a company. However, green accounting does affect firm value. In addition, the correlation between green accounting and firm value and tax avoidance and firm value are both unmodified by corporate social responsibility. The worth of a company is unaffected by tax avoidance, it seems. Green Accounting hurts The value of the enterprise. CSR is unable to act as a mediator between variables related to Tax Avoidance and the value of a firm. However, CSR can influence the link connecting Green Accounting Criteria to Business Value.  Practical implications: The outcomes of this study are expected to help investors make decisions, and it is hoped that this research can develop theories about the value of companies. Originality/value: This research will complement existing research, and what distinguishes it from other research is the CSR variable, which is the moderation variable, where there are still few who include these variables.